Ethics committees and mental health (2018)
ABSTRACT: Although research processes are covered by the objectivity of science, they are still influenced by the interests of those who conduct them. This is why high level committees have been tasked with defining the scope of the studies and performing a thorough assessment of them, since these imply great dilemmas. This premise leads to the emergence of Ethics Committees, where liaison psychiatry has an important place due to its communication abilities and knowledge of the human behaviour. This paper attempts to provide some observations to take into account when discussing the link between ethics and mental health. In this work, the authors approach the question of ethics committees and the importance that psychiatrist performance has within them. This is done through a review of relevant papers on the subject. A detailed description on research ethics is provided in terms of justification, purpose and duties. Likewise, emphasis is placed on each of the areas in which psychiatrists are involved and bear great responsibilities in the medical decision-making process. Similarly, this description also includes the moment in which participants give their informed consent when taking part in medical research. Finally, we conclude that there are several questions regarding the relevance given to these committees in the methodological and ethical assessment of research projects. This in turn implies greater effort in the search for a culture of quality which highlights the emphasis on research subjects.